“Sehalaman Sepermainan Sejamban Seperulangan”: identity and nostalgia in Traditional Malay Houses of Negeri Sembilan - Mohd Nor, Othman; Adham, Khairul; Awaludin, Fazlin; Abd Halim, Norajwani; Abd Rashid, Mohd Sabrizaa; Mohd Isa, Haryati (2024)
"SEHALAMAN SEPERMAINAN SEJAMBAN SEPERULANGAN” are words of advice in “Teromba” or words of advice in Negeri Sembilan custom. It tells about community life in Negeri Sembilan culture. It is associated with the activities that take place in the yard of a traditional Negeri Sembilan house. This study looks at the good relations between neighbours regardless of rank. The yard is the field in front of the residence of every traditional Malay house. The short distance between the yard and the house is used by children, especially in emergencies when the need to use the toilet (Jamban) is urgent. The toilet can be accessed at any time by neighbouring children, emphasizing the community's connection with the environment and the use of natural materials in construction. This study aims to examine the strength of the courtyard within a beautifully landscaped environment, exploring the influence of nature on the architecture of Negeri Sembilan. Rumah Beranjung and Bolomba in Negeri Sembilan embody strong traditional identities through their open-front designs close to nature, offering natural ventilation and comfortable seating, which evoke deep nostalgia among grown-ups who have migrated to the city. The architectural identity of the bolomba house arises from Malay craftsmen's 'local knowledge,' emphasizing observation and dependence on the surrounding nature in its evolution of identity. The overall results of this paper will identify the identity of Rumah Bolomba Negeri Sembilan and produce its architectural elements from the perspective of environmental influence.